2022
DOI: 10.1007/s12011-021-03028-y
|View full text |Cite
|
Sign up to set email alerts
|

No Association Was Found Between Mild Iodine Deficiency During Pregnancy and Pregnancy Outcomes: a Follow-up Study Based on a Birth Registry

Abstract: Background Severe iodine deficiency during gestation is associated with adverse pregnancy outcomes; however, the impact of mild-to-moderate iodine deficiency, though prevalent in pregnancy, remains unclear. Methods We extracted follow-up data for 7435 pregnant women from a national iodine deficiency disorders monitoring program from 2016 to 2018 and a mother–child cohort study in 2017 based on a birth registry in Shanghai. Birth outcomes were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Of these, 53 were identified as potentially relevant after screening of titles and abstracts (with 89% agreement between reviewers) and 26 were identified as relevant following reading of the full texts (with 80% agreement between reviewers). These publications reported on 24 cohorts containing 42,503 participants ( Figure 1 , Supplementary Table S2 ) [ 11 , 12 , 13 , 14 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 53 were identified as potentially relevant after screening of titles and abstracts (with 89% agreement between reviewers) and 26 were identified as relevant following reading of the full texts (with 80% agreement between reviewers). These publications reported on 24 cohorts containing 42,503 participants ( Figure 1 , Supplementary Table S2 ) [ 11 , 12 , 13 , 14 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“… Urinary iodine concentration ( a – c ), iodine to creatinine ratio and birth weight (grams) ( d – f ), dichotomous ( a , d ), linear ( b , e ), and nonlinear ( c , f ) meta-analyses. CI: Confidence interval; Δ: Change in outcome [ 11 , 12 , 13 , 14 , 16 , 28 , 29 , 31 , 33 , 34 , 36 , 37 , 39 , 40 , 41 , 42 , 44 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…I supplementation that began after the 12th wk of pregnancy was associated with significantly low free T4 and a somewhat lower free T3 [ 80 ]. This is supported by a study of women in Tehran ( n = 1286) that found odds of preterm delivery were higher in women with both insufficient and suboptimal thyroid function ( <100 μg/L and TSH ≥ 4 μ /mL) than those with <100 μg/L and TSH <4 μ /mL [ 81 ], and counter to 2 large studies which found mild-to-moderate I insufficiency was not related to worse pregnancy outcomes [ 82 , 83 ]. The final Norwegian study reported a UIC of 79 μg/L and dietary I intake of 140 μg/d, further confirming the I insufficiency of this population [ 84 ].…”
Section: Iodine and Thyroid Function In Pregnancymentioning
confidence: 93%
“…Findings from another 2020 observational study from Tehran showed higher risk of preterm birth in those with deficient UIC and TSH at least 4 mIU/ml [67]. However, two other large observational studies did not find worse pregnancy outcomes associated with MMID [68,69]. A 2023 review of four meta-analysis (MAs) [17,[70][71][72] evaluating the relationship between iodine status and pregnancy and neonatal outcomes suggests a U-shaped correlation between iodine status and maternal and neonatal consequences…”
Section: Iodine and Pregnancy Outcomesmentioning
confidence: 99%